(3GdQbGHI Ydi CYeGd GdSdWI GdbGFeI Ydi MGdI GdWhGQF (B:s (3OQGSI ebGQfI ai GdfXGe GdYQGbi hGdeUQi hGdCfLdh CeQjcis - (3Mbi ESeGYjd HQHhJis; (3KQhJ HOhj s; (3ceGd MTjT s; (3eMeO YUahQ s ((3GdbGgQI (B: s (3Mbi ESeGYjd HQHhJi , s, 1981)
(3HOC JONd GdOhdI aj GdejGOjf GdGbJUGOjI hGdGLJeGYjI hGdSjGSjI efP GdKhQI GdUfGYjI , hGROGO gPG GdJONd GJSGYG haj GdXQha GdGSJKfGFjI , JYhOJ GdHQdeGfGJ GdJQNjU ddgjFI GdJfajPjI HCf JJSdM HLedI GNJUGUGJ GSJKfGFjI Ydi MSGH GdgjFGJ GdCNQi dJhGLg HgG MGdI GdWhGQF , heG Ef TYQJ GdgjFI GdJfajPjI Cf HbOQJgG eeGQSI LGfH ef GNJUGUGJ GdeTQY , hCfgG eJSdMI HgPg GdGNJUGUGJ GdhGSYI GdJj JSJWjY HeHhLHgG JbjjO GdMQjGJ , MJi JTLYJ Ydi GdGfMQGa aj eeGQSI gPg GdGNJUGUGJ , aJYQVJ GdMQjGJ hGdMbhb dCaOM GdCVQGQ , hcGf WHjYjG NdGd Pdc Cf JHQR CgejI GdQbGHI Ydi CYeGd SdWI GdWhGQF s
(3GWQhMI OcJhQGIs
(3jTJed Ydi EQLGYGJ HHdjhLQGajI s
Keywords: (3GdQbGHIs -- (3eUQs; (3MGdI GdWhGQFs -- (3eUQ s